Development of Writing Learning Materials and Indonesian Language Learning Media Using Ms. Powerpoint for Grade VII UPTD SMP Negeri 2 Pulau Rakyat Year 2023-2024 - Agustina; Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
This research was conducted to produce the development of writing materials and learning media for Indonesian learning using Microsoft PowerPoint for grade VII semester 2 students of SMP Negeri 2 Pulau Rakyat. This type of development research data is in the form of qualitative data and quantitative data. The research used the development model and research and development (R&D) of Borg and Gall. The purpose of this research is the compilation of a learning media product as an effort to develop writing material. In connection with this goal, researchers use seven steps in the development of learning media, namely analysis of teacher and student needs, product development with Microsoft PowerPoint, validation of media experts and material experts and Indonesian teachers, the first stage of revision, field trials, and finally the final stage of revision. The quality of learning media products can be known through the average obtained from the validation results of Indonesian teachers of 95%. The average percentage of the assessment results was 87.18% in the very good category. In addition, the quality of development products can also be known through the results of excellent student feedback. This research product is learning materials and media designed for class VII second semester. This product contains eight Competency Standards which are translated into seventeen Basic Competencies and contained in twelve lessons. The twelve lessons are organized and integrated with one main menu. Each media unit is arranged systematically including, perceptions, competency standards and basic competencies, indicators, materials, sample questions and competency tests in which there are various media arranged simultaneously including, text, audio recordings, video and animation. The results of this study are very relevant to the 2013 curriculum because they are in accordance with the standards of the learning process of interactive, inspiring, fun, creative, challenging and motivating students.